ANALISIS BIAYA PEMESANAN DAN BIAYA PEMELIHARAAN DALAM MANAJEMEN PERSEDIAAN BAHAN BAKU (Studi pada PT. Gunawan Dianjaya Steel Tbk) - Fanny Mega Selvia P; Chalim Chalil Yusuf (Faculty of Social and Political Science, 2013)
Inventory is the company's assets that have an important role in business operations, inventory shortages could result in the cessation of the production process and if you are inventory too large (over stock) can result in very high costs to store and preserve the material during storage thus company needs to make proactive inventory management, meaning that the company should he able to minimize the total cost to be incurred related to the supply of raw materialsIn PT Gunawan Dianjaya Steel Corporation, can be seen on the inventory management policies in terms of fees and maintenance costs of raw materials, PT Gunawan Dianjaya Steel Tbk alone can not determine when to hold back ordering or commonly called the reorder point, so the company made a purchase raw materials as much as I Ox within a period of I year during 2010 with a quantity of 286 464 748 kg